ANALISIS PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN PEMECAHAN MASALAH BERBANTUAN KOMIK LITERASI NUMERASI DAN ETNOMATEMATIKA - Aisah, Siti; Panglipur, Indah Rahayu; Sujiwo, Dimas Andita Cahyo (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
The purpose of this research is to find out the application of learning problems (PBL) with the help of comic based literacy numeration and ethnomathematics in the Integrated High School of Madinatul Ulum class VIIIB cangkrung jenggawa based on the theorem pythagoras. This research used qualitative descriptive approaches. The collection of data were observations, interviews, documentation, and tests. Based on a comic-aided problem-solving learning analysis that focuses on the material of the pythagorean theorem and numeration and ethnomathematics literacy, it was found that 80% of students showed improvement. Based on data analysis, it can be concluded that the PBL model improves the learning outcomes of integrated high school students Madinatul Hikmah. The results show that 1. The PBL Model is more attractive to use as a learning model. 2. The students are more involved in working on the pythagoras theorem. 3. The PBL model can improve the critical thinking ability of the pupils and encourage them to do something.